PENGARUH KOMUNIKASI INTERPERSONAL DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MARKETING KELAS XI JURUSAN PEMASARAN DI SMK NEGERI 7 MEDAN TAHUN AJARAN 2024/2025 - Cristi Rahmana G; Aurora Elise Putriku (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of interpersonal communication and self-confidence on students’ learning outcomes in the Marketing subject of Grade XI Marketing Department at SMK Negeri 7 Medan in the 2024/2025 academic year. The research employed a quantitative approach using an ex post facto method. The sample consisted of the entire population, totaling 65 students, who were all selected as respondents through total sampling. The research instruments included questionnaires on interpersonal communication and self-confidence, as well as documentation of students’ learning outcomes. Data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results showed that interpersonal communication had a positive and significant effect on students’ learning outcomes (sig. < 0.05). Self-confidence also had a positive and significant effect on learning outcomes (sig. < 0.05). Simultaneously, interpersonal communication and self-confidence had a positive and significant effect on students’ learning outcomes, with a coefficient of determination (R²) of 0.57. This indicates that 57% of the variation in students’ learning outcomes can be explained by interpersonal communication and self-confidence, while the remaining 43% is influenced by other factors outside this study.